A mediator of OsbZIP46 deactivation and degradation negatively regulates seed dormancy in rice - Naihui Guo; Shengjia Tang; Yakun Wang; Wei Chen; Ruihu An; Zongliang Ren; Shikai Hu; Shaoqing Tang; Xiangjin Wei; Gaoneng Shao; Guiai Jiao; Lihong Xie; et al. (Nature Communications, 2024)
Abstract Preharvest sprouting (PHS) is a deleterious phenotype that occurs frequently in rice-growing regions where the temperature and precipitation are high. It negatively affects yield, quality, and downstream grain processing. Seed dormancy is a trait related to PHS. Longer seed dormancy is preferred for rice production as it can prevent PHS. Here, we map QTLs associated with rice seed dormancy and clone Seed Dormancy 3.1 (SDR3.1) underlying one major QTL. SDR3.1 encodes a mediator of OsbZIP46 deactivation and degradation (MODD). We show that SDR3.1 negatively regulates seed dormancy by inhibiting the transcriptional activity of ABIs. In addition, we reveal two critical amino acids of SDR3.1 that are critical for the differences in seed dormancy between the Xian/indica and Geng/japonica cultivars. Further, SDR3.1 has been artificially selected during rice domestication. We propose a two-line model for the process of rice seed dormancy domestication from wild rice to modern cultivars. We believe the candidate gene and germplasm studied in this study would be beneficial for the genetic improvement of rice seed dormancy.